Analisa NDVI Citra Satelit Landsat Multi Temporal Untuk Pemantauan Deforestasi Hutan Kabupaten Aceh Utara - Meraty Ramadhini; Bangun Muljo Sukojo (Jurnal Inotera, 2017)
One of the functions of the forest is natural disaster such as flood control and the landslide that is how these forests absorb water into the root of the tree. Most forests in North Aceh Regency is protected forest which has undergone deforestation due to the presence of illegal logging and opening of new land like planting oil palm that impact against water infiltration. This research was conducted to identify deforestation forests in 2000, 2003 and 2015 using the techniques of remote sensing by satellite images landsat landsat 7 and 8. The method used was algorithm NDVI to get the classification of forest distribution and the level of deforestation forests based on the density of the vegetation from the Forestry Department 2003. Analysis of the rate of deforestation and loss of vast forests is done by leveraging the value of NDVI and other supporting data.The results showed that the NDVI value for forest distribution based on vegetation density in 2000 was -0,620438 – 0,628743, in 2003 between -0,364238 – 0,530055 and in 2015 between -0,274592 – 0,642049. The rate of deforestation in the district of North Aceh based on the value of the vegetation index (NDVI) yields 3 classes of deforestation are severe deforestation, light deforestation and not deforested, in 2000 there was deforestation of 25,62%, in 2003 it was 99,91% and in 2015 amounted to 15,89%, most deforestation occurs in production forests.